The Power of Proof against CCTV in Criminal Justice System - Tegar Kurnia Priambudi; Lathifah Hanim (Law Development Journal, 2021)
This study aims to determine and analyze the development of the proving power of CCTV in criminal justice, as well as the validity of CCTV as evidence in court.The research approach method used is normative juridical. This research uses qualitative methods with data collection techniques carried out by observation (observation), free in-depth interviews and is supported by literature study. Based on the research, it can be concluded that the function of CCTV recording is to strengthen the Judge's belief in describing the incident at the crime scene recorded in accordance with the facts which are reinforced by the Expert's conviction shown in the CCTV footage and strengthening trial evidence which serves to be used as 2 evidence in court because it is used as a clue and letter. The obstacles faced by the Judge in the process of proving premeditated murder through CCTV footage of the results that were displayed were unclear, due to the location of the CCTV.